Examining intersectional inequalities in access to health (enabling) resources in disadvantaged communities in Scotland: advancing the participatory paradigm - Anuj Kapilashrami; Sara Marsden (BMC, 2018)
Abstract Background Multiple structural, contextual and individual factors determine social disadvantage and affect health experience. There is limited understanding, however, of how this complex system works to shape access to health enabling resources (HER), especially for most marginalised or hard-to-reach populations. As a result, planning continues to be bereft of voices and lived realities of those in the margins. This paper reports on key findings and experience of a participatory action research (PAR) that aimed to deepen understanding of how multiple disadvantages (and structures of oppression) interact to produce difference in access to resources affecting well-being in disadvantaged communities in Edinburgh. Methods An innovative approach combining intersectionality and PAR was adopted and operationalised in three overlapping phases. A preparatory phase helped establish relationships with participant groups and policy stakeholders, and challenge assumptions underlying the study design. Field-work and analysis was conducted iteratively in two phases: with a range of participants working in policy and community roles (or 'bridge' populations), followed by residents of one Edinburgh locality with relatively high levels of deprivation (As measured by the Scottish Index of Multiple Deprivation, a geographically-based indicator. See http://www.gov.scot/Topics/Statistics/SIMD/DataAnalysis/SPconstituencyprofile/EdinburghNorthern-Leith). Traditional qualitative methods (interviews, focus groups) alongside participatory methods (health resource mapping, spider-grams, photovoice) were employed to facilitate action-oriented knowledge production among multiply disadvantaged groups. Results There was considerable agreement across groups and communities as to what healthful living (in general) means. This entailed a combination of material, environmental, socio-cultural and affective resources including: a sense of belonging and of purpose, feeling valued, self-esteem, safe/secure housing, reliable income, and access to responsive and sensitive health care when needed. Differences emerge in the value placed by people at different social locations on these resources. The conditions/aspects of their living environment that affected their access to and ability to translate these resources into improved health also appeared to vary with social location. Conclusion Integrating intersectionality with PAR enables the generation of a fuller understanding of disparities in the distribution of, and access to, HER, notably from the standpoint of those excluded from mainstream policy and planning processes. Employing an intersectionality lens helped illuminate links between individual subjectivities and wider social structures and power relations. PAR on the other hand offered the potential to engage multiply disadvantaged groups in a process to collectively build local knowledge for action to develop healthier communities and towards positive community-led social change.